2017
DOI: 10.1002/elsc.201700020
|View full text |Cite
|
Sign up to set email alerts
|

Anionic lipopeptides from Bacillus mojavensis I4 as effective antihypertensive agents: Production, characterization, and identification

Abstract: A new isolated Bacillus mojavensis strain I4 was found as producer of biosurfactants by different screening methods, such as parafilm M test, hemolytic activity, oil displacement test, emulsification index, surface tension, and lipase production assay. Enhanced biosurfactants production was obtained using glucose and glutamic acid as carbon and nitrogen sources, respectively. The optimal production of the biosurfactants was obtained by using a C/N ratio of 17, pH of 7.0, and temperature of 37°C. The surface te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
5
6
1
Order By: Relevance
“…Surface tension is a key parameter for the evaluation of biosurfactant production.In fact, a microorganism is considered as a promising biosurfactant producer, if it could reduce the surface tension to less than 40 mN m -1 (Shete et al, 2006). The obtained results showed that our biosurfactant is able to reduce surface tension until 30.73mN m -1 ± 0.48 which is lower than results obtained by Ghazala et al(2017) during the characterization of an anionic lipopeptide produced by Bacillus mojavensis I4 where the surface tension of the culture supernatant was 31.5 ± 0.8mN m -1 .Moreover, our results are very close to those obtained by Jemil et al, (2016) which showed that the best result in decreasing surface tension was observed with Bacillus methylotrophicusDCS1 strain (31 mN m -1 ).Likewise, other study showed that biosurfactants produced by O.anthropi HM-1 and C.freundii HM-2 were able to reduce surface tension until 30.8 ± 0.6 and 32.5 ± 1.3 mNm -1 , respectively (Ibrahim 2018). While, compared to surface tensions of some chemical surfactants studied by Ghazala et al (2017), B.safensisF4 cell free broth showed lower surface tension than SDS (34.8±1.3mN m -1 ) and Triton X-100 (32±0.9mN m -1 ).…”
Section: Surface Tension Determinationcontrasting
confidence: 66%
“…Surface tension is a key parameter for the evaluation of biosurfactant production.In fact, a microorganism is considered as a promising biosurfactant producer, if it could reduce the surface tension to less than 40 mN m -1 (Shete et al, 2006). The obtained results showed that our biosurfactant is able to reduce surface tension until 30.73mN m -1 ± 0.48 which is lower than results obtained by Ghazala et al(2017) during the characterization of an anionic lipopeptide produced by Bacillus mojavensis I4 where the surface tension of the culture supernatant was 31.5 ± 0.8mN m -1 .Moreover, our results are very close to those obtained by Jemil et al, (2016) which showed that the best result in decreasing surface tension was observed with Bacillus methylotrophicusDCS1 strain (31 mN m -1 ).Likewise, other study showed that biosurfactants produced by O.anthropi HM-1 and C.freundii HM-2 were able to reduce surface tension until 30.8 ± 0.6 and 32.5 ± 1.3 mNm -1 , respectively (Ibrahim 2018). While, compared to surface tensions of some chemical surfactants studied by Ghazala et al (2017), B.safensisF4 cell free broth showed lower surface tension than SDS (34.8±1.3mN m -1 ) and Triton X-100 (32±0.9mN m -1 ).…”
Section: Surface Tension Determinationcontrasting
confidence: 66%
“…For the dispersant activity of motor oil, slight activations are observed at concentrations ranging from 0.5 to 4% NaCl. These results are similar to numerous previous work reporting the stability of the surface activities of biological surfactants after pre-incubation in the presence of decreasing NaCl concentration (Chen et al 2017, Feng et al 2019, Ghazala et al 2017, Kiran et al 2017, Martins et al 2018, Purwasena et al 2019, Qiao &Shao 2010). This offers a broad spectrum of application of BI2 biosurfactant in the bioremediation of saline and sea waters contaminated by hydrocarbons.…”
Section: Physic-chemical Characterization Of B Mojavensis Bi2 Biosursupporting
confidence: 92%
“…In particular, there is an improvement in the dispersant activity of the oil for heat treatments ranging from 60 to 90°C. Similarly, numerous previous studies reported the stability of the surface activity of lipopeptide biosurfactants (Chen et al 2017, Feng et al 2019, Ghazala et al 2017, Kiran et al 2017, Martins et al 2018, Purwasena et al 2019, Qiao &Shao 2010. As observed in Fig.…”
Section: Physic-chemical Characterization Of B Mojavensis Bi2 Biosursupporting
confidence: 72%
See 1 more Smart Citation
“…Rhamnolipids, sophorolipids, and surfactin are the most widely studied microbial biosurfactants. Their antimicrobial (antibacterial and antifungal), pharmaceutical and medical applications such as anticancer, anti-inflammatory and immunomodulators, antihypertensive activities are well reported in the literature [ 30 , 6 , 29 , 31 ]. More importantly, they have also been active against various viruses.…”
Section: Ecofriendly Hand Hygienementioning
confidence: 99%